Mirounga Gray 1827 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Mirounga Gray 1827 Mirounga Gray 1827, in: Griffith et al., Animal Kingdom, Vol. 5: 179. Type Species: Phoca proboscidea Péron 1816 Synonyms: Macrorhinus F. G. Cuvier 1826; Morunga J. E. Gray 1943; Rhinophoca Wagler 1830. Species and subspecies: 2 species: Species Mirounga angustirostris Gill 1866 Species Mirounga leonina (Linnaeus 1758) Discussion: Revised by King (1966). Reviewed by Davidson (1929), Briggs and Morejohn (1976), and Ling and Bryden (1992). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 597, DOI: 10.5281/zenodo.7316519